(untitled) (Triyuga Academic Journal, 2024)
The purpose of this research article is to describe Buddhist way of funeral rituals of Tāmāṅs, who are the biggest Buddhist indigenous ethnic people of Nepal. They believe cycles of life, reincarnation, good deeds and enlightenment. The rituals that take place around death and funerals are to help the deceased to die in peaceful mind and get nirvana i.e. salvation. They believe in reincarnation and the freeing of the soul. To them, the death is a natural part of the cycle of life and how a person acts throughout their life will determine their future lives after death through reincarnation. Therefore, the death should occur in a calm and peaceful environment with family in attendance. The ultimate goal is to liberate from life and rebirth so they can reach the state of nirvana. To achieve this, they must get rid themselves of worldly desires and all notions of self, ultimately attaining total enlightenment. In the research conducted area, the dead body is found to have been either cremated or buried in ridge. The Buddhist monks i.e. Lamas lead the ceremony. The mourning periods are usually 3rd, 7th, 21st or 49th day after the death of a person. The mourners wear white strips of cloth during the mourning period.